A metastatic ovarian angiosarcoma mimicking hematologic neoplasia at diagnosis - Gaiolla, Rafael Dezen [UNESP]; Duarte, Ivison Xavier; Bacchi, Carlos Eduardo; Paiva, Carlos Eduardo (S. Karger AG, Basel, 2014)
Angiosarcomas are rare aggressive neoplasms of vascular endothelial origin with a high metastatic rate and poor prognosis. Involvement of the bone marrow by the angiosarcoma is exceedingly uncommon, and there have only been a few cases reported in the literature to date. Clinical manifestations and common laboratory findings of bone marrow involvement can mimic other more common bone marrow-replacing neoplasias such as lymphomas and acute leukemia. A definitive diagnosis is difficult to make from cytologic material, probably due to an associated bone marrow fibrosis, and requires bone marrow trephine biopsy with an immunohistochemical profile. Here we had the opportunity to study a case of metastatic angiosarcoma with positive cytologic findings and an unusual presentation that challenged its primary diagnosis.
Keywords: Angiosarcoma; Bone marrow cytology; Bone marrow metastasis; Splenomegaly